2023
DOI: 10.5194/isprs-archives-xlviii-4-w6-2022-183-2023
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessments of Unmanned Aerial Vehicle (Uav) and Terrestrial Laser Scanning (Tls) Methods in Road Cracks Mapping

Abstract: Abstract. In general, poor road conditions, specifically road cracks constitute a public nuisance, causing troublesome to road users, severe damage to vehicles and accidents. Hence, it is essential to detect the road crack earlier as an early-stage preventive for maintenance, but traditional inspection method used in Malaysia to physically collect the road information is extremely time-consuming, hazardous and labour-intensive. Nowadays, new technologies have improved the measuring performance. This leaves a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…The findings reported that using MLS is precise and functional for applications. Yi and Ahmad [26] evaluated using TLS and unscrewed aerial vehicles to determine road crack mapping. Based on the results, it was found that TLS is more accurate and reliable.…”
Section: Introductionmentioning
confidence: 99%
“…The findings reported that using MLS is precise and functional for applications. Yi and Ahmad [26] evaluated using TLS and unscrewed aerial vehicles to determine road crack mapping. Based on the results, it was found that TLS is more accurate and reliable.…”
Section: Introductionmentioning
confidence: 99%